Lampreys and spinal cord regeneration: “a very special claim on the interest of zoologists,” 1830s-present - Maxson Jones, Kathryn; Morgan, Jennifer R. (Frontiers in Cell and Developmental Biology, 2023)
Employing history of science methods, including analyses of the scientific literature, archival documents, and interviews with scientists, this paper presents a history of lampreys in neurobiology from the 1830s to the present. We emphasize the lamprey’s roles in helping to elucidate spinal cord regeneration mechanisms. Two attributes have long perpetuated studies of lampreys in neurobiology. First, they possess large neurons, including multiple classes of stereotypically located, ‘identified’ giant neurons in the brain, which project their large axons into the spinal cord. These giant neurons and their axonal fibers have facilitated electrophysiological recordings and imaging across biological scales, ranging from molecular to circuit-level analyses of nervous system structures and functions and including their roles in behavioral output. Second, lampreys have long been considered amongst the most basal extant vertebrates on the planet, so they have facilitated comparative studies pointing to conserved and derived characteristics of vertebrate nervous systems. These features attracted neurologists and zoologists to studies of lampreys between the 1830s and 1930s. But, the same two attributes also facilitated the rise of the lamprey in neural regeneration research after 1959, when biologists first wrote about the spontaneous, robust regeneration of some identified CNS axons in larvae after spinal cord injuries, coupled with recovery of normal swimming. Not only did large neurons promote fresh insights in the field, enabling studies incorporating multiple scales with existing and new technologies. But investigators also were able to attach a broad scope of relevance to their studies, interpreting them as suggesting conserved features of successful, and sometimes even unsuccessful, CNS regeneration. Lamprey research demonstrated that functional recovery takes place without the reformation of the original neuronal connections, for instance, by way of imperfect axonal regrowth and compensatory plasticity. Moreover, research performed in the lamprey model revealed that factors intrinsic to neurons are integral in promoting or hindering regeneration. As this work has helped illuminate why basal vertebrates accomplish CNS regeneration so well, whereas mammals do it so poorly, this history presents a case study in how biological and medical value have been, and could continue to be, gleaned from a non-traditional model organism for which molecular tools have been developed only relatively recently.